Acoustic impedance of an isotropic medium for rayleigh waves - OPILSKI, Aleksander; URBAŃCZYK, Marian (Archives of Acoustics, 1980)
The acoustic impedance of an isotropic non-piezoelectric medium has been determined for Rayleigh waves. The numerical values of this impedance are very different from the values of the impedance of the medium for a plane bulk wave.